Identifying priority healthcare trainings in frozen conflict situations: The case of Nagorno Karabagh - Dorian Alina H; Thompson Michael E; Harutyunyan Tsovinar L (Conflict and Health, 2010)
Abstract Introduction Health care in post-war situations, where the system's human and fixed capital are depleted, is challenging. The addition of a frozen conflict situation, where international recognition of boundaries and authorities are lacking, introduces further complexities. Case description Nagorno Karabagh (NK) is an ethnically Armenian territory locked within post-Soviet Azerbaijan and one such frozen conflict situation. This article highlights the use of evidence-based practice and community engagement to determine priority areas for health care training in NK. Drawing on the precepts of APEXPH (Assessment Protocol for Excellence in Public Health) and MAPP (Mobilizing for Action through Planning and Partnerships), this first-of-its-kind assessment in NK relied on in-depth interviews and focus group discussions supplemented with expert assessments and field observations. Training options were evaluated against a series of ethical and pragmatic principles. Discussion and Evaluation A unique factor among the ethical and pragmatic considerations when prioritizing among alternatives was NK's ambiguous political status and consequent sponsor constraints. Training priorities differed across the region and by type of provider, but consensus prioritization emerged for first aid, clinical Integrated Management of Childhood Illnesses, and Adult Disease Management. These priorities were then incorporated into the training programs funded by the sponsor. Conclusions Programming responsive to both the evidence-base and stakeholder priorities is always desirable and provides a foundation for long-term planning and response. In frozen conflict, low resource settings, such an approach is critical to balancing the community's immediate humanitarian needs with sponsor concerns and constraints.